Structure-activity relations for the inhibition of catecholamine uptake into synaptosomes from noradrenaline and dopaminergic neurones in rat brain homogenates - Horn, A. S. (1973)
1. The effects of various phenylethylamine analogues on the inhibition of (3)H-noradrenaline and (3)H-dopamine uptake into homogenates of rat hypothalamus and corpus striatum respectively, were examined. 2. Phenolic hydroxyl groups and α-methylation of the side chain were both found to enhance the affinity for the neuronal uptake sites. 3. Methoxylation, β-hydroxylation and N-methylation were all found to reduce the ability of a compound to inhibit catecholamine transport. 4. The noradrenaline and dopamine transport systems responded in a quantitatively different manner to the various phenylethylamine analogues. It was found that, in general, the noradrenaline uptake process was more sensitive to structural changes, both positive and negative, than the dopamine system.